Mauritius : A Competitiveness Assessment - Minoiu, Camelia; Imam, Patrick (Washington, D.C. : International Monetary Fund, 2008)
We assess the competitiveness of Mauritius in recent years using two approaches. First, we estimate the difference between the equilibrium and the actual real exchange rate using four methods: the macroeconomic balance approach, the single-equation fundamentals approach, the capital-enhanced approach, and the external sustainability approach. The methods consistently suggest that at the end of 2007 the exchange rate was aligned with its equilibrium value. Second, we undertake a comparative analysis of structural competitiveness indicators and find that Mauritius often fares better on business climate than other small island economies and high-growth Asian economies. Nevertheless, there are areas for improvement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet